Culturally Responsive Teaching: A Critical Piece in the Development of an African American Woman’s Financial Self-Efficacy/Competency, Relatedness, and Autonomy - Tracie L. Miller-Nobles; Elizabeth A. Roumell; Lisa M. Baumgartner (Adult Education Research Conference, 2022)
This paper presents African American women’s experiences in financial literacy courses. Using culturally responsive teaching, self-efficacy, and self-determination, findings suggest pedagogy that can develop financial self-efficacy/competency, relatedness, and autonomy.
Keywords: culturally responsive teaching; self-efficacy; self-determination; financial literacy; African American women